Doxorubicin Deteriorates the Histomorphology of the Kidneys of Albino Rats - Pandeya, Anup; Jha, Chandra Bhushan; Karki, Smriti; Rauniar, Gajendra Prashad (Journal of Nepalgunj Medical College, 2017)
Background and Objectives: Nephrotoxicity is one of the limiting factors for using doxorubicin as an anticancer chemotherapeutic. Reactive oxygen species and cytokines have been implicated in the nephrotoxicity induced by doxorubicin. The main objective of the present study is to identify and compare the histomorphological features in kidneys of albino rats and gross morphological features such as weight of rats and weight of the kidneys due to administration of doxorubicin. Materials and Methods: In the study, albino rats were taken as the animal model. Sixty animals were taken as the sample size. They were divided into two equal groups: experimental (n=30) and control (n=30). Rats of experimental group were treated with anticancer drug doxorubicin at a single intraperitoneal dose of 10 mg/kg body weight while the Control group of rats received a similar volume of 0.9% normal saline. The ethical clearance was taken prior to the research from IERB committee BPKIHS Dharan. Results: Our results showed that there was high effect of drug in experimental groups of rats. It was seen that there was significant decrease in the body weight and weight of kidneys. The final body weight and kidney weight between experimental and control group showed the significant difference. Similarly there were no significant differences in the normal architecture between the male and female rats. The normal renal histological features were seen on the kidneys in the control group whereas the rats intervened with the drug had some disrupted histological features which reveal the toxicity of the drugs in the kidneys. Conclusion: The study showed toxicity of the drug in the kidneys of experimental groups of rats irrespective of gender and suggest that doxorubicin causes significant loss of the body weight and weight of kidneys and causes the disruption in the normal histological features.